Administrative, Legal and Criminal Aspects of Liability for Illegal Expulsion of Children - Volodymyr Pavlov; Tetiana Slutska; Alina Harkusha; Oleksandr Kozlenko; Oleksandr Sukhomlyn (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
The article provides a detailed analysis of the existing legal acts regarding criminal and administrative liability for the illegal expulsion of children. It has been found that the mass and systematic expulsion of children in the conditions of armed conflict, which is committed by the Russian Federation in the temporarily occupied Ukrainian territories, has signs of three most serious international crimes that belong to the jurisdiction of the International Criminal Court - crimes against humanity, war crimes and crimes of genocide. It is emphasized that the Ukrainian side should continue to try at the international, including the international legal level, to recognize the expulsion of children as genocide. In addition, considerable attention is paid to the peculiarities of international criminal liability for the expulsion of children, the legal status and jurisdiction of the International Criminal Court. The article analyzes the steps that have already been taken in the direction of bringing to justice the officials of the Russian Federation guilty of the expulsion of children. The prospects of making a final decision on this matter and the possibility of its enforcement are considered. At the same time, it is noted that the prospects for the actual execution of a future sentence by an international criminal court are very doubtful, since the Russian Federation is a permanent member of the UN Security Council and has the right to veto any of its decisions. The ineffectiveness of the existing mechanism for bringing to justice not only individuals, but also states in general, even for such international crimes as the deportation of children, which cannot be committed without using the entire state apparatus, has been identified. According to the results of the study, a number of problematic aspects of the current legal regulation and the existing system of international relations in the studied sphere have been identified, recommendations for their overcoming have been formulated.